The Bauru group: a continental Cretaceous unit in Brazil - Concepts based on micropaleontological, oxygen isotope and stratigraphical data - Dias-Brito, D. [UNESP]; Musacchio, E. A. [UNESP]; de Castro, J. C. [UNESP]; Maranhiao, M. S A S [UNESP]; Suárez, J. M. [UNESP]; Rodrigues, R. [UNESP] (My University, 2001)
The integration of outcrop and subsurface information, including micropaleontological data, facies and sequence stratigraphic studies, and oxygen isotope analysis, allow us to present a new stratigraphic model for the Cretaceous continental deposits of the Bauru Group, Brazil. Thirty-eight fossil taxa were recovered from these deposits, including 29 species of ostracodes and 9 species of charophytes. Seven of these ostracode species and three subspecies are new and formally described here. The associations of Chara barbosai - Ilyocypris cf. riograndensis, found in the Adamantina Formation, and Amblyochara sp. - Neuquenocypris minor mineira nov. subsp., found in the Marília Formation. Ponte Alta Member, represent two distinct groups that are respectively Turonian-Santonian and Maastrichtian (probably Late Maastrichtian) in age. Therefore, a hiatus, encompassing more than 11 Ma, separates those two formations. From bottom to top, four depositional cycles were recognized in the Bauru Group in western São Paulo: cycles 1 and 2 belong to Caiuá Formation (fluvio-lacustrine and lacustrine deposits in the Presidente Prudente region), cycle 3 to the Santo Anastácio and lower Adamantina Formation (respectively fluvial and lacustrine deposits), and cycle 4 to the upper Adamantina Formation (fluvio-lacustrine facies). An erosional unconformity separates the Caiuá and Santo Anastácio Formations (between cycles 2 and 3). The Marília Formation is a distinct unit from the underlying succession; it does not occur in western São Paulo, but is found in restricted areas of São Paulo, Minas Gerais, Mato Grosso do Sul and Goiás States. During the deposition of the Bauru Group (Aptian? to Maastrichtian) the climate was hot and arid-semiarid. Shallow lakes underwent fluctuations in expansion (wet phases) and contraction (dry phases), as well as variations in salinity. During the deposition of the Adamantina Formation (Turonian-Santonian) there were long, dry periods that caused segmentation of large lakes (due to topographic irregularities in the basaltic substrate) and sometimes exposures of the lake floors; when flooded these lake floors were colonized by extensive meadows of single species of charophytes. Small ephemeral ponds, that were hydrochemically unstable and colonized by multiple species of charophytes, were the depositional sites for the marls and mudstones of Ponte Alta Member (Maastrichtian, Late Maastrichtian?). Our micropaleontological age control, combined with the Late Cretaceous ages of volcanic ashes found in the southeastern Brazil coastal basins, and the stratigraphic position of analcimites from the Jaboticabal-SP region, suggest a Late Coniacian-Santonian age for important magmatic events occurred in the interior of Brazil (north-central São Paulo State, Triângulo Mineiro, and southwestern Goiás State).
Grupo Bauru: uma unidade continental do Cretáceo no Brasil - concepções baseadas em dados micropaleontológicos, isotópicos e estratigráficos
Keywords: Bauru group; Brazil; Charophyta; Continental cretaceous; Ostracoda; Paleoecology; Stratigraphy; Biostratigraphy; Cretaceous; Oxygen isotope; Paleoecology; Paleoenvironment; Sequence stratigraphy